The Dissonance of "Doing Good": Fostering Critical Pedagogy to Challenge the Selective Tradition of Nonprofit Management Education. (3rd September 2022) - Feit, Maureen Emerson; Sandberg, Billie
Abstract: Nonprofit management classrooms are filled with students who yearn to "do good" in the world and yet, in practice, they confront a dissonance between their vision of doing good and the realities of nonprofit work. This dissonance is in part created by contemporary nonprofit management education (NME) through the development and perpetuation of a selective historical tradition of the nonprofit sector which mythologizes the sector and its work. These traditions and myths of the nonprofit sector are based squarely in white American and Eurocentric values and downplay the histories of people of color and thus perpetuate whiteness as central to nonprofit norms and practice. We present a critical reading of these histories in an effort to help educators and students reclaim and reimagine the histories of the nonprofit sector and offer tenets of a critical pedagogy that emphasizes historical consciousness and a praxis of emancipation so that nonprofit educators and students can re-envision nonprofit theory and practice in the future.